2021
DOI: 10.3892/or.2021.7955
|View full text |Cite
|
Sign up to set email alerts
|

LRPPRC contributes to the cisplatin resistance of lung cancer cells by regulating MDR1 expression

Abstract: The development of multidrug resistance is the major obstacle to successful lung cancer chemotherapy. Cancer cells gain resistance through increased levels of P-glycoprotein (P-gp), which is encoded by the multidrug resistance-associated protein 1 (MDR1) gene. Leucine-rich PPR motif-containing protein (LRPPRC), a member of the PPR family, has been verified to regulate the transcription of MDR1. This regulation is influenced by the methylation status of the GC -100 box in the MDR1 promoter. The present study ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Previous studies have reported that the drug transporter genes MRP1 and MDR1 mediated the development of platinum drug resistance in lung cancer cells [18,19]. Moreover, nucleotide excision repair and base excision repair mechanisms are also said to be able to protect against the cytotoxicity of cisplatin in cancer cells [20].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the drug transporter genes MRP1 and MDR1 mediated the development of platinum drug resistance in lung cancer cells [18,19]. Moreover, nucleotide excision repair and base excision repair mechanisms are also said to be able to protect against the cytotoxicity of cisplatin in cancer cells [20].…”
Section: Discussionmentioning
confidence: 99%
“…The role of this protein is unknown and may play a role in cytoskeletal organization, vesicular transport, or in transcriptional regulation of both nuclear and mitochondrial genes. Various studies demonstrate that high expression of LRPPRC is associated with poor prognosis in a variety of cancers, such as bladder urothelial carcinoma [39], lung cancer [40] and pancreatic cancer [41]. Maimaiti [42] et al de ned LRPPRC as a N6methyladenosine (m6A) modi cation for intracranial aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports indicated that CTD-3252C9.4 is abnormally expressed in multiple cancers. It is found highly expressed in head and neck cancers, hepatocellular carcinoma, colon and ovary cancer [ 13 , 17 ], while significantly reduced in prostate, uterus, breast, and kidney cancers[ 12 ], which indicated that CTD-3252C9.4 has diverse expression patterns in different cancers. The roles of CTD-3252C9.4 in nasopharyngeal and hepatocellular carcinomas have been revealed.…”
Section: Discussionmentioning
confidence: 99%
“…Increased CTD-3252C9.4 expression was markedly associated with aggressive clinicopathological factors and shorter survival time in patients with hepatocellular carcinoma. Through binding with EZH2 to inhibit E-cadherin expression, CTD-3252C9.4 contributes to hepatocellular carcinoma cell invasion and migration [ 17 ]. The expression and function of CTD-3252C9.4 in pancreatic cancer, however, have not been reported so far.…”
Section: Discussionmentioning
confidence: 99%